Idealo ir tikrovės santykis valstybės tarnyboje: retrospektyvus žvilgsnis į etikos problemas tarpukario Lietuvos Respublikoje - Palidauskaitė, Jolanta (Lietuvos istorijos studijos, 2011)
The purpose of this study was to analyze the relationship between the ideal and reality in the First Lithuanian Republic when the foundations of contemporary Lithuanian civil service were laid down. Various scientists and Lithuanian legislators were involved in the construction of the ideal of civil service, but the reality and the image of the reality in media were different. So, the author had a goal to compare these two dimensions: the ideal constructed by scientists and the image reflected in the media. Attention was given also to ethical problems in civil service. The construction of the ideal portrait of civil servant, or civil service in general, was not among the primary state goals, so the majority of studied publications were published in 1926---1939. This was important for economists, lawyers, specialists of management, to mention just a few - A. Baliūnas, G. Galvanauskas, V. Graičiūnas, P. Lesauskis, S. Nacevičius, P. Raulinaitis, J. Šimkus, etc. Some of them had studied at western universities and were familiar with the newest managerial theories or were writing themselves on various questions including state administration or governance.Some topics such as an ideal organization, the role of individual in organizational settings, the ideal of a leader, state administration and civil service, the ideal of a civil servant were considered by scientists as more important and were elaborated in detail in their articles or books. How important were such attempts? Their model of state governance, sketches of ideal organization, leaders, civil servants, etc. can be considered an attempt to introduce Lithuanian public with new theoretical concepts and provide some necessary knowledge creating foundations of the new state.Lithuanian legislator, earlier than scientists, tried to introduce the model for civil servants, emphasizing certain aspects of their activity or indicating some restrictions. The first laws regulating the activity of civil servants were passed as far back as 1919 and 1920. The Lithuanian legislators creating the ideal could not encompass so many issues so their attention was limited and concentrated mainly on the organizational aspects of civil service or the requirements to civil servants. Later, legislators were not able to supplement the ideal, and even the Law on Civil Service existed in draft.Before analyzing the image of reality reflected in the media, the author stresses some points that help to better understand the position of journalists. Critical analyses of certain problems in the Lithuanian public sphere helped lawyers, economists, specialists of management and public figures in constructing the ideal model. Meanwhile media representatives and those whose opinion was published were often apt to overdraw, dramatize the existing problems or present them as dominating models. The best illustration is the very negative stereotype of a public servant. Taking into consideration the fact that journalists often are more interested in abnormal things, that can be estimated as scandalous, the author concludes that an honest civil servant properly performing his official duties is not an exception. Critical publications in the media allow distinguishing some positive changes in the activities of civil servants or public institutions which have notably improved the competence of their staff and the quality of its functioning.